Biocomposites based on oil palm tree as packaging materials - Wan Abdul Rahman, Wan Aizan; Rasit Ali, Roshafima; Wan Hasan, Wan Hasamuddin; Muhammad Tajudin, Izzati Nazreen (2007)
Every parts of the oil palm tree can be utilized to form useful products, including the waste from palm oil processing either intermediates or final biomasses. Utilization oil palm wastes and palm oil product will be presented for the application in the packaging industry, especially as environmental friendly packaging materials. For the development of these new biodegradable packaging materials, product and waste from oil palm tree are compounded to form biocomposites. Empty fruit bunch, waste that is derived after palm oil extraction process, is grinded and compounded with polyethylene to form biocomposites for blow film process. Palm cooking oil (PCO) is used as processing aids/lubricant in the blown film processing of low density polyethylene with empty fruit bunch fiber (LDPE/EFB) to form biofilm. This oil ease the process ability of LDPE/EFB on the conventional blown film thermoplastic machinery. The higher the composition of the PCO the better will be the processability of LDPE/FFB as the resistance to flow is decreased. With PCO composition greater than 2% the processing parameters of LDPE can be used to process LDPE/PCO/EFB into film. Tensile properties of the biocomposite film are found to be dependent on the PCO composition and comparable to the polyethylene film at low PCO composition. As the composition of PCO in LDPE/EFB is increased the tensile strength and elongation at break of the biofilm is decreased.